Color Filters: Plasmonic Color Filter and its Fabrication for Large‐Area Applications (Advanced Optical Materials 2/2013). Issue 2 (22nd February 2013) - Do, Yun Seon; Park, Jung Ho; Hwang, Bo Yeon; Lee, Sung‐Min; Ju, Byeong‐Kwon; Choi, Kyung Cheol
<x xml:space="preserve">Abstract</x> A plasmonic color filter (PCF) containing a metallic nanohole array is described by B.‐K. Ju, K. C. Choi, and co‐workers. This new PCF can be fabricated on an extremely large scale compared to the currently available alternatives, and the process can be adapted to create a flexible product. This is possible by using laser interference lithography based on Lloyd's mirror, as shown in the bottom left of the front cover image. The metal layer is positioned between two dielectric layers (which are different from the substrate), allowing high transmission. The filtering of all primary colors (red, green, and blue) is demonstrated on page 133. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>